Comportamento mecânico de solos artificialmente cimentados: ensaios modelagem e aplicação - Oliveira, Alex Duarte de (2015)
Considering the similarity between the mechanical behavior of artificially cemented soils and rock masses, this study proposes a methodology to obtain the envelopes resistance of artificially cemented soils, using the Hoek-Brown failure criterion. The proposed methodology consists basically in performing two triaxial tests, with the soil non-cemented and cemented with a high cement content, and estimate the strength envelopes for intermediate cement contents, using the equations presented in this research. To develop the methodology, initially, a number of unconfined compression tests and triaxial tests were carried out in order to quantify the influence of the porosity/cement ratio (n/Civ) on the strength parameters of the cement mixtures used. From the tests results and the Hoek-Brown failure criterion, new equations were developed to calculate the envelope parameters (a, m, s), as functions of porosity/cement ratio. The proposed method was applied to triaxial tests data presented in four different studies and the results showed that the Hoek-Brown envelope is suitable to represent the resistance of artificial cemented soils, being able to incorporate the effects caused by the confining pressure and by the cement content. The envelopes estimated and those obtained from the triaxial tests were very close, indicating that the proposed methodology can be used with a reasonable degree of reliability. The results obtained with the proposed methodology were used to simulate, by the Finite Element Method, the pressuresettlement behavior and the variation of the safety factor of a shallow foundation bearing on a double-layered system formed by an artificially cemented soil layer overlaying a soil stratum. The simulations were performed using as variables the cement content of the enhanced layer and the relationship between the thickness of the treated layer (H) and the diameter of the foundation (D). The results show that the use of artificially cemented layers considerably increases the vertical pressure required for an specific settlement and also the foundation safety factor. Thus, the execution of shallow foundations, replacing deep foundations, becomes feasible